Proposition d’une trame de recherche pour appréhender la capacité d’adaptation au changement climatique - Alexandre Magnan (VertigO)
A generally accepted idea consists in systematically linking a low level of adaptive capacity to a low level of development, and then in affirming that the poor have inevitably low adaptive capacities. What we argue here is that this affirmation is biased because adaptation to climate change is not only determined by economic and technological capacities. Many other characteristics of a community could play a major function in its ability to react to and to anticipate climate changes (e.g. the territorial identity or the social relationships). From our point of view, the generally restrictive conception of adaptive capacity is related to a relative immaturity of the science of adaptation to explain what are the processes and the determinants of adaptive capacity. This can be explained by the fact that few frameworks for studying adaptive capacity currently exist. This paper then consists in a proposition of a research framework based upon four main fields of investigation: (i) the influential factors of adaptive capacity and their interactions, (ii) the relevant spatial and temporal scales of adaptive capacity, (iii) the links between adaptive capacity, vulnerability and the level of development and (iv) the theoretical links between adaptation and sustainability. These four fields of research are assumed to be relevant to bring new knowledge on adaptive capacity, and then to feed a more general reflection on the adaptation pathways to deal with climate change.